Alteration of N-glycoproteins/N-glycosites in human hepatic stellate cells activated with transforming growth factor-Î²1 - Qin, Y; Wang, Q; Zhong, Y; Zhao, F; Wu, F; Wang, Y; Ma, T; Liu, C; Bian, H; Li, Z (Cellular and Molecular Biology, 2016)
Proteins N-glycosylation is significantly increased in the activated human hepatic stellate cells (HSCs) stimulated by transforming growth factor-Î²1 (TGF-Î²1) compared to the quiescent HSCs according to our previous study. However, little is known about the alteration of N-glycoprotein profiles in the activated HSCs. Profiles of N-glycopeptides / N-glycoproteins / N-glycosites in LX-2 cells, with and without activation by TGF-Î²1, were identified and compared using hydrazide chemistry enrichment coupled with liquid chromatography - mass spectrometry analysis. Western blot and immunohistochemistry were further used for validation. A total of 103 non-redundant N-glycopeptides, with 107 glycosylation sites from 86 N-glycoproteins, were identified in activated and quiescent LX-2 cells respectively. Among these, 23 proteins were known N-glycoproteins, and 58 were newly identified N-glycoproteins. In addition, 43 proteins (e.g., pigment epithelium-derived factor and clathrin heavy chain 1) were solely identified or up-regulated in the activated LX-2 cells, which participated in focal adhesion and glycosaminoglycan degradation pathways and were involved in interaction clusters of cytoskeletal proteins (e.g., myosin light chains and keratins). The increased expression of glucosamine (N-acetyl)-6-sulfatase and phospholipase C beta 2 and the decreased expression of zinc finger and BTB domain-containing protein 1 were validated in the activated compared to the quiescent LX-2 cells. In conclusion, increased expression of N-glycoproteins and N-glycosites play important roles in cellular contractility, signal transduction, and responses to stimuli in the activated HSCs, which might provide useful information for discovering novel molecular mechanism of HSC activation and therapeutic targets in liver fibrosis.